In vivo and ex vivo methods of growing a liver bud through tissue connection - Yusuke Yanagi (Nature Portfolio, 2017)
Abstract Cell-based therapy has been proposed as an alternative to orthotopic liver transplantation. The novel transplantation of an in vitro-generated liver bud might have therapeutic potential. In vivo and ex vivo methods for growing a liver bud are essential for paving the way for the clinical translation of liver bud transplantation. We herein report a novel transplantation method for liver buds that are grown in vivo involving orthotopic transplantation on the transected parenchyma of the liver, which showed long engraftment and marked growth in comparison to heterotopic transplantation. Furthermore, this study demonstrates a method for rapidly fabricating scalable liver-like tissue by fusing hundreds of liver bud-like spheroids using a 3D bioprinter. Its system to fix the shape of the 3D tissue with the needle-array system enabled the fabrication of elaborate geometry and the immediate execution of culture circulation after 3D printing—thereby avoiding an ischemic environment ex vivo. The ex vivo-fabricated human liver-like tissue exhibited self-tissue organization ex vivo and engraftment on the liver of nude rats. These achievements conclusively show both in vivo and ex vivo methods for growing in vitro-generated liver buds. These methods provide a new approach for in vitro-generated liver organoids transplantation.